Migration, Schizophrenia, and Crime: A Study From a Forensic Psychiatric Sample - He, Yong; Gu, Yan; Wang, Shujian; Li, Yan; Li, Gangqin; Hu, Zeqing (Frontiers in Psychiatry, 2022)
Background: The association between mental health problems and crime in immigrants has attracted recent academic interest, with results suggesting that there were possible interactions between immigration, schizophrenia, and criminal behavior. However, very few studies have examined these interactions, especially in developing countries that have mass internal immigration. Therefore, this study sought to identify the associations between the sociodemographic, clinical, and criminal factors in migrant and non-migrant Chinese schizophrenia patients who had been involved in criminal activities. Methods: The demographic, clinical, and criminal activity information for suspects who had been referred for criminal responsibility assessments and diagnosed with schizophrenia in the Sichuan West China Forensic Centre Archives from January 2015 to December 2019 were reviewed and evaluated using psychiatric and social function assessment scales. A Chi-squared test, a T-test, a Mann-Whitney U test, and Multinomial logistic regression were employed for the statistical analysis. Results: A total of 552 patients were reviewed and evaluated, 17.2% (n = 95) of which were migrants. The migrant patient group was younger than the non-migrant patient group, the Brief Psychiatric Rating Scale (BPRS) and Social Disability Screening Schedule (SDSS) scores for the migrant patient group were lower than for the non-migrant patient group, the migrant patient group had a stronger history of employment and more had been employed at the time of the crime than the non-migrant patient group, and the unemployed migrant patients were more likely to commit property-related crime. Conclusions: Compared to the non-migrant schizophrenia patient group, the migrant patient group had less severe psychiatric symptoms, fewer social functioning impairments, and a higher rate of property-related crime. Employment was an important factor for preventing criminal activity, so that schizophrenia patients and especially migrant patients need to receive focused vocational rehabilitation.